2022
DOI: 10.3390/ijerph19031430
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Problems among Young People—A Scoping Review of Help-Seeking

Abstract: Young people’s mental health is a public health priority, particularly as mental health problems in this group seem to be increasing. Even in countries with supposedly good access to healthcare, few young people seek support for mental health problems. The aim of this study was twofold, firstly to map the published literature on young people’s experiences of seeking help for mental health problems and secondly to validate whether the Lost in Space model was adaptable as a theoretical model of the help-seeking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 38 publications
0
20
0
2
Order By: Relevance
“…The same barrier was commonly reported by a third of the youth with a higher degree of depression and suicidality in one study [21] and the fth in another [16]. Possible explanations could be provided; young people aspire to hold more responsibility for their health problems, aiming for acquiring more strength and weakness avoidance [22], [23]. Besides, the majority of the Egyptian students in a previous study showed dissatisfaction with the provided mental health care system [24]; this might urge them to search for alternative solutions.…”
Section: Discussionmentioning
confidence: 57%
“…The same barrier was commonly reported by a third of the youth with a higher degree of depression and suicidality in one study [21] and the fth in another [16]. Possible explanations could be provided; young people aspire to hold more responsibility for their health problems, aiming for acquiring more strength and weakness avoidance [22], [23]. Besides, the majority of the Egyptian students in a previous study showed dissatisfaction with the provided mental health care system [24]; this might urge them to search for alternative solutions.…”
Section: Discussionmentioning
confidence: 57%
“…It is widely reported that CYP who need support for their mental health do not always access services (Anderson, Howarth, Vainre, Jones, & Humphrey, 2017; Lewis, 2021; Westberg, Nyholm, Nygren, & Svedberg, 2022). Previous reviews exploring CYP's experiences of help‐seeking for mental health problems showed that support structures are often seen as inaccessible and unresponsive (Anderson et al, 2017; Westberg et al, 2022). Our systematic review identified numerous moderate confidence synthesis statements related to CYP's barriers and facilitators to seeking and accessing appropriate support at the point of crisis.…”
Section: Discussionmentioning
confidence: 99%
“…An array of scientifically validated treatment protocols exist for intervention across the range of psychiatric disorders and diagnoses; however, their efficacy can be blunted by numerous impediments to successful outcome. These may include social barriers such as actual or perceived stigma, practical complications regarding accessibility and availability of suitable treatment, and attrition, among others (Westberg et al , 2022; Hamilton et al , 2022) and have been exacerbated by the COVID-19 pandemic (Pierce et al , 2021; Probst et al , 2020; Czeisler et al , 2020).…”
Section: Introductionmentioning
confidence: 99%